Identification of potential districts for the implementation of industrial synergies applicable to manufacturing MSMEs from Lima Metropolitan Area - Prada Alvarez, Aldair Edison (2023)
Industrial synergies (ISs) are practices designed to optimize the use of resources by employing solid waste and discarded material, such as raw materials, thus promoting a sustainable and continuous cycle in industrial production and consumption. The methodology of this research included a documentary analysis with a qualitative approach and descriptive scope aimed at identifying potential districts in Lima Metropolitan Area for implementing ISs applicable to manufacturing micro, small, and medium-sized enterprises (MSMEs). The results indicate that the textiles and apparel industry group is the one with the largest number of manufacturing MSMEs. Furthermore, the districts of Lima Metropolitan Area with the greatest potential for the implementation of ISs are San Juan de Lurigancho, Ate, Santiago de Surco, and San Martín de Porres. These results allow an understanding of the opportunities and challenges for the transition toward a circular economy in the industrial sector, providing a basis for future proposals and sectoral strategic actions.